1938
DOI: 10.1113/jphysiol.1938.sp003622
|View full text |Cite
|
Sign up to set email alerts
|

The thermal decomposition of visual purple

Abstract: IN 1878 Ewald & Kiuhne measured the time necessary for.solutions of visual purple to become decolourized completely when heated to various temperatures. They also investigated the effects of NaCl and of the absence of water on the thermal bleaching, and concluded that the reactions were very similar to the coagulation of albumen by heat. Since very little is known about the chemical nature of visual purple, it was decided to extend these observations by making some quantitative measurements of its thermal blea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1939
1939
1988
1988

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…The effect of temperature on the thermal bleaching of rhodopsin has been described by Lythgoe and Quilliam (1938; cf. their Fig.…”
Section: N___b ----E_~lnr ' Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of temperature on the thermal bleaching of rhodopsin has been described by Lythgoe and Quilliam (1938; cf. their Fig.…”
Section: N___b ----E_~lnr ' Nmentioning
confidence: 99%
“…or above it bleaches rapidly in the dark and at a rate that is very temperature-dependent. Lythgoe and Quilliam (1938) calculated an experimental activation energy of 44 kg. cal.…”
mentioning
confidence: 99%
“…Recent investigations by Lythgoe and Quilliam (1938) suggest th a t visual purple is bleached by interaction with the solvent water molecules. If this is the case it is easy to see how a quantum efficiency of unity might arise-the visual purple chromophore grouping is presumably surrounded by water molecules with which it may react when it has absorbed a light quantum.…”
Section: Discussionmentioning
confidence: 99%
“…5 a, 56) for which R. temp were used. The solutions were buffered to a pH of 9-3 and were maintained a t constant temperature in the range between 19 and 27° C, where the thermal decomposition was negligible (Lythgoe and Quilliam 1938). The cells used for the experiments had areas, as follows: nos.…”
Section: R Esultsmentioning
confidence: 99%
“…Hosoya (8) described "Nachbleichung" first and it was confirmed by Wald (9) and Lythgoe (4). And Lythgoe (4,10) reported that the indicator yellow solution was unstable at pH6.5-3.5 and decomposed thermally at this pH range especially at pH5.2. The exhibition of a deeper yellow color in the retina TH2 at the final stadium of bleaching which I observed, occurred at this range of pH only.…”
mentioning
confidence: 99%